Perancangan dan Promosi Toko Online Produk Makanan Berbasis Opencart Di Kecamatan Simpang Kiri - Ramadhan Pratama, Aldi; Annas, Firdaus (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The Simpang Kiri sub-district, one of the areas that is in the process of developing, Simpang Kiri sub-district needs a platform to make it easier for food sellers to reach wider product promotions. The solution for food sellers in Simpang Kiri sub-district can be implemented by building an opencart-based online shop, an e-commerce platform that is flexible and easy to implement. This research aims to design an opencart-based online shop for food products in Simpang Kiri sub-district, and make it easier to sell and attract the attention of consumers. The development model used in this research is a research and development model with an analysis, design, development, implementation and evaluation approach. The conclusion of this research shows that using Opencart as an e-commerce platform can make it easier for food sellers in Simpang Kiri sub-district to promote their products. Therefore, with the right design and effective promotion, if the promotion runs effectively, the Simpang Kiri sub-district will develop rapidly, reach more consumers and be wider.